2023
DOI: 10.3390/s23020839
|View full text |Cite
|
Sign up to set email alerts
|

On-Device Intelligence for Malfunction Detection of Water Pump Equipment in Agricultural Premises: Feasibility and Experimentation

Abstract: The digital transformation of agriculture is a promising necessity for tackling the increasing nutritional needs on Earth and the degradation of natural resources. Toward this direction, the availability of innovative electronic components and of the accompanying software programs can be exploited to detect malfunctions in typical agricultural equipment, such as water pumps, thereby preventing potential failures and water and economic losses. In this context, this article highlights the steps for adding intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…More specifically, students verified the functionality of the two systems by creating water misuse events (Figure 9a) via repositioning the valves of the pumping system (Figure 9b), and monitoring the corresponding results on their mobile phone screens. The recorded results indicated that 9 over 10 predictions were correct, which is in line with the performance of each machine-learning system, as explained in [29,30].…”
Section: Technical Aspectsupporting
confidence: 79%
See 2 more Smart Citations
“…More specifically, students verified the functionality of the two systems by creating water misuse events (Figure 9a) via repositioning the valves of the pumping system (Figure 9b), and monitoring the corresponding results on their mobile phone screens. The recorded results indicated that 9 over 10 predictions were correct, which is in line with the performance of each machine-learning system, as explained in [29,30].…”
Section: Technical Aspectsupporting
confidence: 79%
“…To that end, this paper takes into consideration the material provided by two studies that use machine learning techniques for developing detection systems in order to address typical irrigation network problems. The first one introduces a water-misuse alert system [29], while the second one utilizes a classification model to detect water pump malfunctions in agricultural premises [30]. This article, except from providing a brief technical overview, is trying to explain how the latter systems can be transformed into effective educational instruments, suitable for serving the priorities of an agricultural engineering laboratory.…”
Section: Related Work and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Cloud, Internet of Things, Big data and IA 1) Cloud: computing plays a crucial role in smart farming, which is an application of the Internet of Things (IoT) in agriculture. The cloud enables farmers to store, process, and analyze large amounts of data generated from various IoT devices and sensors on their farms [9]. This data can include information on weather patterns, soil moisture levels, crop growth, and even the health of livestock.…”
Section: A Unnamed Aerial Vehicles For Agriculturementioning
confidence: 99%
“…ML has been widely adopted for prediction tasks in various domains, including healthcare [7], disease prevention [8], environmental science [9], and the energy sector itself [10,11]. In the industry sector, the use of ML is even more extensive for early fault detection and the condition monitoring of industrial equipment [12][13][14][15]. These studies showed that such techniques could improve equipment reliability, reduce downtime and maintenance costs, and increase operational efficiency.…”
Section: Introductionmentioning
confidence: 99%